Evaluasi Usability Pengembangan Website Desa Wisata Bejiharjo Gunung Kidul Yogyakarta - Atun Yulianto (Journal of Tourism and Economic, 2019)
A website that has an easy-to-use user interface for visitors to interact (usability) or communicate in sharing information is needed by web visitors. This study aims to provide an assessment of the website developed by Bejiharjo tourism village from the perspective of web visitors, in terms of the interactivity (usability) function of the website interface in general. Besides that it also aims to find out website development strategies to increase website usability by web managers. The research method used is a qualitative descriptive method that is supported by SWOT analysis to develop discussions to the discovery of website development strategies. The results of this study are IFAS (internal factor analysis summary) score from the analysis of the website obtaining a score of no more than 2.5. While the EFAS score (external factors analysis strategy) obtained a score of 2.87. This score shows that the opportunities and threats to the development of the Bejiharjo tourism village website are greater than the strengths and weaknesses. Therefore we need a development strategy based on a SWOT analysis that includes adding types of social media accounts that are connected to the website, maintaining continuity with website content updates, increasing the detail of information on the main website content, equipping the website with video content, reservation forms and visitor comment columns.